The Impact of Mobile Legends on the Emotional Intelligence of PAI UMY Students - Alim, Ansorul; Madjid, Abdul (Transpublika Publisher, 2024)
The rising popularity of online games like Mobile Legends serves as both entertainment and a platform for social interaction. However, on the other hand, this game also has the potential to influence emotional intelligence, an important skill for prospective educators such as students of Department of Islamic Education (PAI) at University of Muhammadiyah Yogyakarta (UMY). This study aims at analyzing the impact of the Mobile Legends game on the emotional intelligence of PAI students at UMY, with social skills as a mediating variable. This research used a descriptive quantitative approach with inferential analysis. Data were collected through closed-ended questionnaires distributed to the population (census sampling), consisting of 63 PAI students who play Mobile Legends. Data analysis was performed using simple linear regression and the Sobel test to examine direct and indirect relationships (through social skills as a mediator) between variables. The results showed that the Mobile Legends game had a positive impact on students’ emotional intelligence, both directly with a contribution of 53.61%, and indirectly through social skills as a mediator with a contribution of 44.78%. However, an unbalanced and improper intensity of play can potentially lead to negative impacts on emotional management skills. The study concludes by emphasizing the importance of maintaining balanced gaming habits to maximize emotional intelligence benefits while mitigating potential risks to students' emotional well-being.